Preliminary investigations for better monitoring: Learning in repeated insurance audits - Reda Aboutajdine; Pierre Picard (Risks, 2018)
Audit mechanisms frequently take place in the context of repeated relationships between auditor and auditee. This paper focuses attention on the insurance fraud problem in a setting where insurers repeatedly verify claims satisfied by service providers (e.g., affiliated car repairers or members of managed care networks). We highlight a learning bias that leads insurers to over-audit service providers at the beginning of their relationship. The paper builds a bridge between the literature on optimal audit in insurance and the exploitation/exploration trade-off in multi-armed bandit problems.
Keywords: 330; ex-post moral hazard; insurance fraud; optimal auditing; learning